Answer:
![m = (1)/(12)](https://img.qammunity.org/2022/formulas/mathematics/college/259u5xa2gbun8sgnrohek69nrgrywu77hx.png)
Explanation:
Given
![(x,y) = (36,6)](https://img.qammunity.org/2022/formulas/mathematics/college/eh42qeuwp7f240985cw56tt9af1aywlq94.png)
----- the equation of the curve
Required
The slope of f(x)
The slope (m) is calculated using:
![m = \lim_(h \to 0) (f(a + h) - f(a))/(h)](https://img.qammunity.org/2022/formulas/mathematics/college/bhokea5u2aqn7ebl4hvosn6h14fkr4hdtq.png)
implies that:
![a = 36; f(a) = 6](https://img.qammunity.org/2022/formulas/mathematics/college/o7m20mmumj4fscmvqowmsnqchs9iujh89j.png)
So, we have:
![m = \lim_(h \to 0) (f(a + h) - f(a))/(h)](https://img.qammunity.org/2022/formulas/mathematics/college/bhokea5u2aqn7ebl4hvosn6h14fkr4hdtq.png)
![m = \lim_(h \to 0) (f(36 + h) - 6)/(h)](https://img.qammunity.org/2022/formulas/mathematics/college/lefo1gde0bkbbftjf0w37dxnpjst8mn1xa.png)
If
; then:
![f(36 + h) = √(36 + h)](https://img.qammunity.org/2022/formulas/mathematics/college/31jkpkfoy3obcwjxzbrvxfztbmsjsc0sp1.png)
So, we have:
![m = \lim_(h \to 0) (√(36 + h) - 6)/(h)](https://img.qammunity.org/2022/formulas/mathematics/college/gc2v6squ978j8980ez4quy7fz23yh9vcb8.png)
Multiply by:
![√(36 + h) + 6](https://img.qammunity.org/2022/formulas/mathematics/college/lf8vdzma6oke808la7u8jgm90yfwi4jwrj.png)
![m = \lim_(h \to 0) ((√(36 + h) - 6)(√(36 + h) + 6))/(h(√(36 + h) + 6))](https://img.qammunity.org/2022/formulas/mathematics/college/vl2mgbykreofc14ucq4ju34851otjvpl65.png)
Expand the numerator
![m = \lim_(h \to 0) (36 + h - 36)/(h(√(36 + h) + 6))](https://img.qammunity.org/2022/formulas/mathematics/college/guw2q358f8zdvze85e0rl6psfdqch7m5yj.png)
Collect like terms
![m = \lim_(h \to 0) (36 - 36+ h )/(h(√(36 + h) + 6))](https://img.qammunity.org/2022/formulas/mathematics/college/fmwq7tee9isyttgout2vjjz3fczzpufk4e.png)
![m = \lim_(h \to 0) (h )/(h(√(36 + h) + 6))](https://img.qammunity.org/2022/formulas/mathematics/college/8qmaja44wazbkw41659imlwmutgybmb1sv.png)
Cancel out h
![m = \lim_(h \to 0) (1)/(√(36 + h) + 6)](https://img.qammunity.org/2022/formulas/mathematics/college/emvhmh4o6wfhxcxaj1mzdpnompoc1e1low.png)
implies that we substitute 0 for h;
So, we have:
![m = (1)/(√(36 + 0) + 6)](https://img.qammunity.org/2022/formulas/mathematics/college/d56tjtbsdv540tlp1886xoxjrequ7hv1e1.png)
![m = (1)/(√(36) + 6)](https://img.qammunity.org/2022/formulas/mathematics/college/vln70s5f6o8tl5fj6d4xspv7phpz6ilyeg.png)
![m = (1)/(6 + 6)](https://img.qammunity.org/2022/formulas/mathematics/college/fosoox65ym6mafdztx4umzaxar3ar7oqk6.png)
![m = (1)/(12)](https://img.qammunity.org/2022/formulas/mathematics/college/259u5xa2gbun8sgnrohek69nrgrywu77hx.png)
Hence, the slope is 1/12